Biological aspects of radiation in nuclear medicine - Kotzerke, J.; Oehme, L. (Nuklearmedizin - NuclearMedicine, 2010)
Radiotherapy with unsealed radionuclides differs from external radiotherapy with regard to the radiation quality and energy range, the regional dose uniformity and the time course of irradiation regimen. External radiotherapy is planned precisely and can be applied to a target volume independently from blood flow during a course of irradiation fractions. In contrary, administered radiopharmaceuticals distribute according to their pharmacokinetic properties and generate a continuous irradiation corresponding to the effective halflife. The resulting dose rates are approximately 1 Gy/min and 1 Gy/h, respectively. The bio – kinetics of radiopharmaceuticals involves cellular accumulation and retention with highly variable affinity to specific organs that can be modulated as well. A remarkable dose gradient is found at the edge of volumes with enhanced uptake. The biological effect of an irradiation with decreasing intensity can be compared with the radiation effect caused by conventional fractionation with 2 Gy a day in external beam therapy by means of the linear-quadratic model. However, the experimental validation of this translation is still under investigation. Radionuclide therapy is usually performed in several cycles some month apart. This procedure fails to meet external radiotherapy. The vision of a combined external-internal radiotherapy requires efforts for a common dosimetry approach both in vitro and in vivo with a physical and biological verification of the results.
Keywords: Radiotherapy; radionuclide therapy; dosimetry; BED; radiation tolerance